Respuesta :
Let [tex]a=[/tex]the length of the shorter leg
Let [tex]b=[/tex]the length of the longer leg
Let [tex]c=[/tex]the length of the hypotenuse
[tex]b=a^{2}-5[/tex]
[tex]c=2a^{2}-13[/tex]
Pythagorean Theorem:
[tex]c^{2}=a^{2}+b^{2}[/tex]
⇒[tex](2a^{2}-13)^{2}=a^{2}+(a^{2}-5)^{2}[/tex]
Substitute a new variable [tex]n[/tex] into [tex]a^{2}[/tex]
⇒[tex](2n-13)^{2}=n+(n-5)^{2}[/tex]
⇒[tex]4n^{2}-52n+169=n+n^{2}-10n+25[/tex]
⇒[tex]4n^{2}-52n+169=n^{2}-9n+25[/tex]
⇒[tex]3n^{2}-43n+144=0[/tex]
⇒[tex](3n-16)(n-9)=0[/tex]
⇒[tex]n=\frac{16}{3}[/tex] or [tex]n=9[/tex]
Since 9 is a perfect square, we go with [tex]n=a^{2}=9[/tex]
⇒[tex]a=3[/tex]
Plug [tex]a[/tex] into [tex]b=a^{2}-5[/tex]
⇒[tex]b=3^{2}-5[/tex]
⇒[tex]b=9-5[/tex]
⇒[tex]b=4[/tex]
Plug [tex]a[/tex] into [tex]c=2a^{2}-13[/tex]
⇒[tex]c=2(3)^{2}-13[/tex]
⇒[tex]c=18-13[/tex]
⇒[tex]c=5[/tex]
So the triangle is a 3-4-5 right triangle.
Let [tex]b=[/tex]the length of the longer leg
Let [tex]c=[/tex]the length of the hypotenuse
[tex]b=a^{2}-5[/tex]
[tex]c=2a^{2}-13[/tex]
Pythagorean Theorem:
[tex]c^{2}=a^{2}+b^{2}[/tex]
⇒[tex](2a^{2}-13)^{2}=a^{2}+(a^{2}-5)^{2}[/tex]
Substitute a new variable [tex]n[/tex] into [tex]a^{2}[/tex]
⇒[tex](2n-13)^{2}=n+(n-5)^{2}[/tex]
⇒[tex]4n^{2}-52n+169=n+n^{2}-10n+25[/tex]
⇒[tex]4n^{2}-52n+169=n^{2}-9n+25[/tex]
⇒[tex]3n^{2}-43n+144=0[/tex]
⇒[tex](3n-16)(n-9)=0[/tex]
⇒[tex]n=\frac{16}{3}[/tex] or [tex]n=9[/tex]
Since 9 is a perfect square, we go with [tex]n=a^{2}=9[/tex]
⇒[tex]a=3[/tex]
Plug [tex]a[/tex] into [tex]b=a^{2}-5[/tex]
⇒[tex]b=3^{2}-5[/tex]
⇒[tex]b=9-5[/tex]
⇒[tex]b=4[/tex]
Plug [tex]a[/tex] into [tex]c=2a^{2}-13[/tex]
⇒[tex]c=2(3)^{2}-13[/tex]
⇒[tex]c=18-13[/tex]
⇒[tex]c=5[/tex]
So the triangle is a 3-4-5 right triangle.
The lengths of the boundaries are 3, 4 and 5 miles respectively
Represent the boundaries with x, y and z, where:
- x represents the shorter leg
- z represents the hypotenuse
So, we have:
[tex]y = x^2 - 5[/tex]
[tex]z = 2x^2 - 13[/tex]
By Pythagoras theorem, we have:
[tex]z^2 =x^2 + y^2[/tex]
This gives
[tex](2x^2 - 13)^2 = x^2 + (x^2 - 5)^2[/tex]
Expand the equation
[tex]4x^4 - 52x^2 + 169 = x^2 + x^4 - 10x^2 + 25[/tex]
Collect like terms
[tex]4x^4 -x^4 - 52x^2 -x^2 +10x^2 + 169 - 25=0[/tex]
[tex]3x^4 -43x^2 + 144=0[/tex]
Factorize
[tex](3x^2 - 16)(x^2 - 9) = 0[/tex]
Split
[tex]3x^2 = 16\ or\ x^2 = 9[/tex]
The boundaries are whole numbers. So, we discard one of the solutions.
So, we have:
[tex]x^2 = 9[/tex]
Solve for x
[tex]x = 3[/tex]
Recall that:
[tex]y = x^2 - 5[/tex]
[tex]z = 2x^2 - 13[/tex]
So, we have:
[tex]y = 9 -5=4[/tex]
[tex]z = 2(9) - 13 = 5[/tex]
Hence, the lengths of the boundaries are 3, 4 and 5 miles respectively
Read more about Pythagoras theorems at:
https://brainly.com/question/654982